The Rance tidal power station: Toward a better understanding of sediment dynamics in response to power generation. (December 2022) - Rtimi, Rajae; Sottolichio, Aldo; Tassi, Pablo
Abstract: A three-dimensional coupled hydrodynamic and morphodynamic numerical model was developed to analyze sediment dynamics in the Rance estuary, in response to the tidal power station (TPS) built near the mouth in the 1960s. The Rance estuary is a relatively small low-discharge steep-sided ria, located along the Brittany coast in northern France, with a maximum spring tidal range of 13.5m. Taking advantage of this significant tidal regime, the first and currently the second largest operational tidal power station in the world was built at the estuary's mouth, with peak output capacity of 240MW. After calibration and validation of the model for present-day conditions, suspended sediment concentration (SSC) and bed level evolution were evaluated at tidal and fortnightly scales for different scenarios, with and without TPS. Peak SSC are reached during spring tides and specifically during the estuary's infilling (flood) stage where both turbines and sluice gates are open. Unbalanced with sediment transport during ebb, sediments are accumulated in the main channel of the upper estuary. Under natural tidal forcing (i.e., without TPS), simulations show that an estuarine turbidity maximum forms in the upper estuary, and sediment deposition is significant. However, sedimentation rates are two times lower than those observed in the presence of the TPS. A possible alternative for reducing sediment accumulation in the upper estuary would be the opening of sluice gates simultaneously with the turbines during falling tide, to enhance ebb currents that would allow particles transport towards the estuary's downstream.